On the Solvability of a Resonant Third-Order Integral m-Point Boundary Value Problem on the Half-Line - O. F. Imaga; J. G. Oghonyon; P. O. Ogunniyi (Abstract and Applied Analysis)
In this work, the existence of at least one solution for the following third-order integral and m-point boundary value problem on the half-line at resonance ρtu′t″=wt,ut,u′t,u″t,t∈0,∞,u0=∑j=1m αj∫0ηj utdt,u′0=0,limt⟶∞ρtu′t′=0, will be investigated. The Mawhin’s coincidence degree theory will be used to obtain existence results while an example will be used to validate the result obatined.